2007
DOI: 10.1007/s00248-006-9163-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cultivated and Uncultivated Actinobacterial Endophytes in the Stems and Roots of Rice

Abstract: A dual approach consisting of cultivation and molecular retrieval of actinobacterial 16S rRNA genes was used to characterize the diversity of actinobacterial community inhabiting interior of rice stems and roots. Streptomyces is the most frequently isolated genus from rice stems and roots. Forty-five clones chosen randomly among 250 clones in the 16S rRNA gene clone library from roots were affiliated with nine genera of actinobacteria and uncultured actinobacteria (Mycobacterium, Streptomyces, Micromonospora, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 30 publications
3
48
1
2
Order By: Relevance
“…They are being used as ingredients in medicinal and cosmetic preparations [40]. Recently, it was documented that the essential oil has antiinflammatory, antioxidant and anti-proliferative capacities [41]. The present study showed that the essential oil has wide varieties of volatile oil terpene hydrocarbons (aliphatic and cyclic) and their corresponding isoprenoid derivatives and analogues, mixtures of these substances, terpinen-4-01 demonstrated fraction that strongly antimicrobial effect by acting only in eukaryotic bacteria cell as in Table 1 and Figures 1 and 2 and this finding is in agreement with [42].…”
Section: Discussionmentioning
confidence: 99%
“…They are being used as ingredients in medicinal and cosmetic preparations [40]. Recently, it was documented that the essential oil has antiinflammatory, antioxidant and anti-proliferative capacities [41]. The present study showed that the essential oil has wide varieties of volatile oil terpene hydrocarbons (aliphatic and cyclic) and their corresponding isoprenoid derivatives and analogues, mixtures of these substances, terpinen-4-01 demonstrated fraction that strongly antimicrobial effect by acting only in eukaryotic bacteria cell as in Table 1 and Figures 1 and 2 and this finding is in agreement with [42].…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic actinobacteria, as one of the significant residents in plant tissues, have attracted more attention in recent years since there is an ever increasing need for novel organisms and their bioactive products. There have been numerous reports focusing on these useful microorganism, which have been isolated from diverse economic plants such as wheat (Coombs and Franco 2003), rice (Tian et al 2007), potato (Sessitsch and Berg 2004), carrots (Surette et al 2003), tomato, rape (Nejad and Johnson 2000) and citrus (Araujo et al 2002) and various medicinal plants (Taechowisan et al 2003;Zin et al 2007;Li et al 2008;Qin et al 2009). These organisms seem to have important roles in plant development and health because they can promote plant growth by nutrient assimilation or phytohormone production.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic actinobacteria have attracted attention in recent years, with increasing reports of isolates from a range of plant types, including crop plants (cereals, such as wheat and rice, as well as potatoes, carrots, tomatoes, and citrus) (2,16,62,71,74,80) and medicinal plants (75,88). The culturable endophytic actinobacteria from these plants were found to fall within a narrow species distribution: Streptomyces spp.…”
mentioning
confidence: 99%